THE ROLE OF ARTIFICIAL INTELLIGENCE IN HIGHER EDUCATION LANGUAGE TEACHING - Suyarova Mavjuda Ergashevna (Ta'lim innovatsiyasi va integratsiyasi, 2026)
Abstract.  Artificial  Intelligence  (AI)  has  become  one  of  the  most  influential technological  innovations  in  modern  education.  In  higher  education,  especially  in language teaching, AI is reshaping traditional pedagogical approaches by introducing personalized  learning  systems,  intelligent  tutoring,  automated  assessment,  and interactive  communication  tools.  This  paper  analyzes  the  role  of  AI  in  language education, its pedagogical benefits, challenges, and future development trends. The study shows that AI significantly improves learning efficiency, student motivation, and teacher productivity, while also raising ethical and methodological concerns.